Ninth Five Year Plan 1997-2002 Volume-VIII Government of Assam - Planning Commission (Planning Commission, 1997)
The Planning Commission has proposed an allocation of Rs. 17.40 crores (Rupees seventeen crores forty lakhs) for Hill Areas of Assam for the 9th Plan period (1997-2002); and an allocation of Rs. 2.00 (two) crores has been approved for Hill areas Assam for the Annual Plan 1997-90. The Schematic allocation for the 9th Plan period as well as for the Annual Plan 1997-98
Government of Assam